Guru Dituntut, Guru Menuntut - Muhammad Irsyad (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Purwokerto, 2015)
: the emergence of Act number 14, 2005 (Undang-Undang Nomor 14 tahun 2005) actually mean answer question about teacher problems. Until now, teacher always demanded to have professional skill and competency. However, on the other side, the consequence accepted did not equal with effort exertion for teacher profession. Teacher and lecturer act try to answer several problems about right and obligation of teacher and lecturer, even its implementation still far from what is teacher hoping and demanded.